Advances in Mechanical Engineering Selected Contributions from the Conference "Modern Engineering: Science and Education", Saint Petersburg, Russia, June 2016 - Evgrafov, Alexander N. (Lecture Notes in Mechanical Engineering,, 2017)
This book draws together the most interesting recent results to emerge in mechanical engineering in Russia, providing a fascinating overview of the state of the art in the field in that country which will be of interest to a wide readership. A broad range of topics and issues in modern engineering are discussed, including dynamics of machines, materials engineering, structural strength and tribological behavior, transport technologies, machinery quality and innovations. The book comprises selected papers presented at the conference "Modern Engineering: Science and Education", held at the Saint Petersburg State Polytechnic University in 2016 with the support of the Russian Engineering Union. The authors are experts in various fields of engineering, and all of the papers have been carefully reviewed. The book will be of interest to mechanical engineers, lecturers in engineering disciplines and engineering graduates.